Penyesalan di Usia Lanjut - Rini, Rini (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
about things they did or didn’t at their young age. This research aims to find out what people regret in their old age so that it can be a positive reflection for the younger generation. Subjects in this study were 20 elderlies with aged over 60 years. The sampling technique used is the Accidental Sampling technique. Data collection by depth interviews with subjects. Data analysis was carried out using a qualitative descriptive approach. The results of the analysis show that regret in old age is divided into two, namely personal regret and social regret. Personal regrets consist of they did not managed their financials well, did not dare to follow their own will, were not getting married, they chose not to have children, they were afraid of taking risks, lived overdriven by worries, always feeling insecure, and lived their lives too seriously. Social regret consists of they were always trying to please everyone, they chose the wrong friends, took their partner for granted, they were too strict to their children, prioritizing work over others, chose the wrong life partner, the constant needs to feel appreciated, and living in hatred.